Notes on the floral morphology and phenology of Bacurizeiro (Platonia insignis Mart.) Clusiaceae in Bragança, Pará - Batista, Fábio de Jesus; Jardim, Mário Augusto Gonçalves (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
Information on floral morphology, fruiting and flowering phenology were presented. This research was carried out in a natural population located in Benjamin Constant community, municipality at Bragança, northeast of Pará State. Seven individuals of natural population were studied on phenology since this appearing of floral button at fruiting maturation. This description of floral morphology was made with lupa ZEISS. Platonia insignis Mart. is hermafrodite, showy flowers, solitary and roseate located in branch terminals, pedunculate, cyclical and radial simetry; flowering from August to December and fruiting from November to March. This specie presented partial synchronism and annual pattern for flowers and fruits.
Keywords: Floral morphology; Secondary vegetation; Platonia insignis; Phenology